2019
DOI: 10.1039/c9sm00932a
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of linear battacin lipopeptides – the effect of lengthening fatty acid chain

Abstract: Explaining antimicrobial battacin lipopeptides by investigating the solution structure – the propensity to aggregate may have a role in a declined antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Furthermore, SAR studies enabled via Ala scanning allowed for optimization of the lipidated linear analogue sequence. Indeed, Kihara et al confirmed the significance of the N-terminal lipid, demonstrating the tendency for different lipidated battacin analogues to form various aggregation shapes depending on the lipid present, which correlated to differences in antibacterial activity . Inspired by this work, the Brimble group sought to further probe the SAR of battacin through generation of a library of linear analogues bearing various lipids installed using CLipPA S -lipidation (Scheme ).…”
Section: Antibiotics Against Gram-negative Bacterial Infectionsmentioning
confidence: 94%
“…Furthermore, SAR studies enabled via Ala scanning allowed for optimization of the lipidated linear analogue sequence. Indeed, Kihara et al confirmed the significance of the N-terminal lipid, demonstrating the tendency for different lipidated battacin analogues to form various aggregation shapes depending on the lipid present, which correlated to differences in antibacterial activity . Inspired by this work, the Brimble group sought to further probe the SAR of battacin through generation of a library of linear analogues bearing various lipids installed using CLipPA S -lipidation (Scheme ).…”
Section: Antibiotics Against Gram-negative Bacterial Infectionsmentioning
confidence: 94%
“…To overcome the toxicity of naturally occurring battacin, we previously designed and synthesized novel structural analogs . Remarkably and in contrast to other AMPs, such as polymyxin, two of these linear peptides, octapeptide 17 (hereafter octapeptide) and its derivative pentapeptide 30 (hereafter pentapeptide) (Figure ), were found experimentally to be active, in terms of both lysing bacteria and dispersing preformed biofilms, against both model Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria. , Unlike many AMPs, ,, the activity of these battacin analogs does not rely on the presence of a defined secondary structure when bound to the membrane, , suggesting that the mechanism of action might also differ. It is extremely difficult to experimentally obtain a detailed atomic level insight into their mechanism of action, however.…”
Section: Introductionmentioning
confidence: 99%